PROPOSING GUIDELINES FOR PHISHING VICTIMIZE BASED ON HEURISTIC SYSTEMATIC MODEL - Ting, Li Shan, author; Ganthan Narayana Samy, Dr., supervisor; Sekolah Informatiks Termaju (Kuala Lumpur : Universiti Teknologi Malaysia, 2015)
Thesis (Sarjana Sains (Jaminan Maklumat))-Universiti Teknologi Malaysia, 2016